Africa Would Need to Import More Maize in the Future Even Under 1.5°C Warming Scenario. Issue 1 (13th January 2021) - Zhai, Ran; Tao, Fulu; Lall, Upmanu; Elliott, Joshua
Abstract: Producing enough food to feed a growing population is a great future challenge, especially for vulnerable areas in Africa. There is limited understanding of food security under future climate conditions, particularly under the warming target stipulated in the Paris Agreement. Maize is the most widely cultivated crop in Africa. Taking maize as an example, we present an integrated assessment of maize supply and demand under 1.5°C and 2.0°C warming scenarios, considering the combined impacts of climate change, technology development and population increase. We find that global warming of 1.5°C or 2.0°C would shorten maize growth duration, aggravate droughts, and consequently reduce yield with a spatially explicit pattern. Maize yield would decrease more under global warming of 2.0°C versus 1.5°C. Benefit of rising CO2 concentration could not fully offset the yield loss due to climate change under global warming of 1.5°C. Technology development can significantly improve the ratio of maize supply to demand, which is however subject to future projections on population and technology development. Under a reasonable logarithmic technology development scenario, maize security would become worse in most of the countries in Africa. Our findings highlight the importance of technology development and adaptation strategies to meet the challenges of food security in the vulnerable regions. Key Points: Maize yield would decrease more under 2.0 than 1.5°C warming scenario Under a reasonable logarithmic technology development scenario, maize security would become worse in most of the countries in Africa Technology development and adaptation strategies are essential to meet the challenges of food security in the vulnerable regions